2021
DOI: 10.1186/s12887-021-02762-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acute diarrhea and associated factors among children under five in semi-urban areas of northeastern Ethiopia

Abstract: Background Diarrheal disease is still one of the most common causes of mortality and morbidity in children under five in developing countries, including Ethiopia. Lack of specific data on the prevalence of acute diarrhea and associated factors among under-five children in the semi-urban areas of Gelsha, found in northeastern Ethiopia’s South Wollo zone, remains a major gap. Therefore, this study was designed to provide data that is important for proper planning of intervention measures to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
2
15
1
1
Order By: Relevance
“…Regarding the type of source of drinking water, our study showed that the likelihood of diarrhea was 50% higher among respondents who rely on unimproved drinking water sources. This finding is in line with the study conducted in north Ethiopia ( 30 ), south Ethiopia ( 31 ), west Ethiopia ( 32 ), northwest Ethiopia ( 29 ), and northwest Tigray ( 33 ). This could be attributed to the fact that unprotected water sources have a higher likelihood of being fecal-contaminated than unprotected water sources.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the type of source of drinking water, our study showed that the likelihood of diarrhea was 50% higher among respondents who rely on unimproved drinking water sources. This finding is in line with the study conducted in north Ethiopia ( 30 ), south Ethiopia ( 31 ), west Ethiopia ( 32 ), northwest Ethiopia ( 29 ), and northwest Tigray ( 33 ). This could be attributed to the fact that unprotected water sources have a higher likelihood of being fecal-contaminated than unprotected water sources.…”
Section: Discussionsupporting
confidence: 92%
“…The results of another study in Bangladesh support our observation indicating that the prevalence of diarrhea in children under age 5 declined from 13.7% at baseline to 3.6% at the end line of the WASH intervention area. 41 Similarly, Getahun et al 42 and Natnael et al 43 highlighted that unimproved sanitation facilities, practicing unsafe child feces disposal, and poor handwashing practices at critical times were significantly associated with acute diarrhea among children under 5 years in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The first component is problem identification involving community surveillance must be conducted to determine the burden, disease causative agent [62], high risk areas, characteristics of cases and other related factors of waterborne diarrhea diseases. The second component is Identification and quantifying of risks factors in the community should be done focusing on water supply, sanitation, and hygiene (hand washing) the major risk factors of waterborne diarrhea diseases [61,63] and other demographic, social economic behavioral and environmental related factors [64]. This should be followed by identification of evidence-based intervention(s) based on the risk's factors identified.…”
Section: Proposed Frameworkmentioning
confidence: 99%